Children's neural processing of moral scenarios provides insight into the formation and reduction of in‐group biases. Issue 6 (25th April 2018) - Meidenbauer, Kimberly L.; Cowell, Jason M.; Decety, Jean
Abstract: Survival is dependent on sociality within groups which ensure sustenance and protection. From an early age, children show a natural tendency to sort people into groups and discriminate among them. The computations guiding evaluation of third‐party behaviors are complex, requiring integration of intent, consequences, and knowledge of group affiliation. This study examined how perceiving third‐party morally laden behavior influences children's likelihood to exhibit or reduce group bias. Following a minimal group paradigm assignment, young children (4–7 years) performed a moral evaluation task where group affiliations and moral actions were systematically juxtaposed, so that they were exposed to disproportionately antisocial in‐group and prosocial out‐group scenarios. Electroencephalography was recorded, and group preference was assessed with a resource allocation game before and after the EEG session. Across all children, evaluations of others' moral actions arose from early and automatic processing (~150 ms), followed by later interactive processing of affiliation and moral valence (~500 ms). Importantly, individual differences in bias manifestation and attitude change were predicted by children's neural responses. Children with high baseline bias selectively exhibited a rapid detection (~200 ms) of scenarios inconsistent with their bias (in‐group harm and out‐group help). Changes in bias corresponded to distinct patterns in longer latency neural processing. These new developmental neuroscience findings elucidate the multifaceted processing involved in moral evaluation of others' actions, their group affiliations, the nature of the integration of both into full judgments, and the relation of individual differences in neural responses to social decision‐making in childhood. Abstract : Perceiving third‐party morallyladen behavior influences children's likelihood to exhibit or reduce group bias. Both electroenphalographic and behavioral results demonstrate that children are capable of prioritizing kindness and helpfulness over similarity.